If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + 2 = 17 Reorder the terms: 2 + 5z = 17 Solving 2 + 5z = 17 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5z = 17 + -2 Combine like terms: 2 + -2 = 0 0 + 5z = 17 + -2 5z = 17 + -2 Combine like terms: 17 + -2 = 15 5z = 15 Divide each side by '5'. z = 3 Simplifying z = 3
| -29-10n=-18n+9 | | a=x | | -4n+3=13 | | 14x+23=4x+173 | | 11-2x+8x+5=32 | | r+1/3=8/3 | | (x^2-2x)-180=0 | | 9=g+3 | | -(12-4x)+8(10-4x)= | | 34=t+15 | | x-5/3=10 | | 5(3x-4)+2=4(3x+2) | | 7+8x=98.2 | | -2/5y=-4/15 | | 15.99x-26.73=42.72 | | 0.05s+0.10(6000-s)=375 | | x+2=4(4x-6) | | 3x-5=1x-13 | | 7*0+8y=7 | | 6x^2+2x+2=150 | | 0.06p+0.08(1600-p)=65 | | -14=2x-8 | | 144.54=2.55h+73.14 | | .99k-27=42.72 | | -5x-10=14-3x | | -p=8 | | 2-x=-3x-4 | | 6p/5=8p-4/3 | | -480=-20(-6b) | | 3(2x-5)-4(5x-2)= | | -4x+5/11+3x-3/11=4/11 | | 11p-17p=12 |